2018
DOI: 10.1016/j.chemgeo.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of noble gases and SF6, as tracers of CO2 flow through porous sandstone

Abstract: A B S T R A C TIn order to label the CO 2 injected underground for geological storage and allow it to be differentiated from natural sources, a panoply of additive chemical tracers have been proposed. Yet, the transport of these tracers relative to CO 2 in pore space is currently poorly constrained. This leads to uncertainty as to whether tracers will act as an early warning of CO 2 arrival, or be preferentially retained in the pore space making them ineffective. Here, we present the factors affecting transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…, for the PMCH tracer, arrival times vary tremendously for different depths within each observation well. There are distinct flow pathways, created by sinuous fluvial channels between the injector and the observation wells, which respond differently to the pressure responses caused by changes in injection rate (similar to the effects seen in the core‐scale experiments by Kilgallon et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, for the PMCH tracer, arrival times vary tremendously for different depths within each observation well. There are distinct flow pathways, created by sinuous fluvial channels between the injector and the observation wells, which respond differently to the pressure responses caused by changes in injection rate (similar to the effects seen in the core‐scale experiments by Kilgallon et al …”
Section: Resultsmentioning
confidence: 99%
“…Fluvial depositional systems clearly have a dramatic impact on solute transport in the subsurface in both single and multiphase flow problems because the preferential pathways account for the majority of mass transport. 7,8,34,[49][50][51][52][53][54][55] Recently, Kilgallon et al 56 compared the travel times of noble gases and SF 6 tracer in sandstone core samples, and found that the heterogeneity play a key role at the core-scale as well. They also found that different molecules had different travel times at core-scale level.…”
Section: Breakthrough Curves In Observation Wells F2 and F3mentioning
confidence: 99%
“…Sulfur hexafluoride (SF 6 ) is a common tracer gas that has been used as a surrogate for RNGs in the past (e.g., Carrigan et al, and ; Stauffer et al, ) because of its relatively low cost to obtain and to analyze, low background concentration (9 parts per trillion) in the atmosphere, and the very small subsurface‐gas samples needed for analysis (e.g., 100 cc) to achieve high detection sensitivity in the parts‐per‐trillion range. A laboratory study by Kilgallon et al () shows similar breakthrough times for both xenon and SF 6 mixed with CO 2 carrier gas passing through sandstone samples. However, a recent laboratory study involving adsorption of both xenon and SF 6 gases on rock surfaces under near‐vacuum conditions suggests that xenon has higher adsorption while moving through the rock mass (e.g., Paul, ; Paul et al, ) causing its breakthrough (i.e., reaching a sampling station) to be retarded at a given concentration compared to SF 6 .…”
Section: Introductionmentioning
confidence: 85%
“…Heat jackets were placed around both the core holder and the syringe pumps to maintain the system at the required test temperature. The fluid was sampled at the outlet of the core and subsequently analyzed with a quadrupole mass spectrometer (QMS), which measures gas concentration (Freifeld & Trautz, 2006; Kilgallon et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Chemical tracers have been used extensively to study the movement and interactions of gases, liquids, and solids in a wide range of fields, including environmental science (Myers et al, 2013). Recently, chemical tracers have been applied to carbon dioxide (CO 2 ) geosequestration studies (Bachaud et al, 2011; Fagerlund et al, 2013; Flude et al, 2016; Freifeld, 2005; Freifeld & Trautz, 2006; Györe et al, 2015; Hovorka et al, 2013; Kilgallon et al, 2018; Lu et al, 2012; Rasmusson et al, 2014; Roberts et al, 2017; Soltanian et al, 2018; Stalker et al, 2015; Strazisar et al, 2009; Watson & Sullivan, 2012; Zhang et al, 2011). Sulfur hexafluoride (SF 6 ), perfluorocarbon tracer (PFT), and noble gases, such as krypton (Kr) and xenon (Xe), have been widely used in CO 2 geosequestration studies due to their unreactive nature.…”
Section: Introductionmentioning
confidence: 99%